2010
DOI: 10.1140/epjb/e2010-00115-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tournaments: the soccer case

Abstract: Abstract. A random walk-like model is considered to discuss statistical aspects of tournaments. The model is applied to soccer leagues with emphasis on the scores. This competitive system was computationally simulated and the results are compared with empirical data from the English, the German and the Spanish leagues and showed a good agreement with them. The present approach enabled us to characterize a diffusion where the scores are not normally distributed, having a short and asymmetric tail extending towa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…This approach has been successfully applied to a variety of fields, from physics and astronomy [6] to genetics [7] and economy [8]. Moreover, this framework has been a trend towards investigating and modeling interdisciplinary fields, such as religion [9], elections [10], vehicular traffic [11], tournaments [12], and many others. These few examples and social phenomena in general [13] illustrate as physicists have gone far from their traditional domain of investigations.…”
mentioning
confidence: 99%
“…This approach has been successfully applied to a variety of fields, from physics and astronomy [6] to genetics [7] and economy [8]. Moreover, this framework has been a trend towards investigating and modeling interdisciplinary fields, such as religion [9], elections [10], vehicular traffic [11], tournaments [12], and many others. These few examples and social phenomena in general [13] illustrate as physicists have gone far from their traditional domain of investigations.…”
mentioning
confidence: 99%
“…It has been indicated that measures, called V r and W r , independent of the empirical law functional form, lead to subsequent numerical results pointing to some inner structure of the team rank-value distribution, according to the present set of UEFA rules. It can be guessed, without more mathematical work than is necessary, that the inner structure is likely tied to the pool, in the first rounds, followed by the "direct elimination" tournament-like process [40] in UEFA competition, and the "increase in value" of the team when progressing further in the competitions through an accelerating effect. with a set of nonlinear constraints (similar to boundary conditions) inducing an unstable organization, similar to what is found in intermittent processes, when forced cycles drive an interplay between (two or several) feedback mechanisms and leading to visible physically characterized zones [59].…”
Section: Discussionmentioning
confidence: 99%
“…Each element P i→j of P gives the ball-passing probability from the node i to the node j. The transition matrix is also normalized as N j=1 P i→j = 1 (7) for each i. Note that the transition matrix is not necessarily symmetric.…”
Section: Markov-chain Modelmentioning
confidence: 99%
“…From the viewpoint of physics, studies with respect to football games are considered to be classified into the following two types: mechanical and statistical. In the latter case, goal distribution [2,3,4,5] and outcome prediction of football games [6,7,8,9] have been studied for example. A football game can be considered as a dynamical system in which game players interact with each other via one ball.…”
Section: Introductionmentioning
confidence: 99%